Effect of Explant’s Size and Phytohormonal Composition of Nutritive Medium on Post-Vitrification Recovery of Garlic Meristems - Vitsenia, Tamara I.; Ivchenko, Tatyana V.; Shevchenko, Nadiya O.; Stribul, Tamara F. (Problems of Cryobiology and Cryomedicine, 2015)
Investigation of the effect of explants dimensions and composition of nutritive medium on morphometric parameters of devitrified garlic meristems will enable a significant optimizing of the cryopreservation techniques intended to establish a collection of its cultivars at low temperature bank. Apexes were subjected to dehydration with plant vitrification solution (1M sucrose + 2M glycerol + 2.5 M ethylene glycol based on Murashige-Skoog salt medium) for 120 min, placed into a polypropylene container and immersed into liquid nitrogen. Thawing was performed in a water bath at 40Â°C, washing of cryoprotectants was carried-out by a two-fold transfer into the medium with 0.3 Msucrose. It has been shown that the solution under study was non-toxic to garlic meristems and allowed the obtaining of a high level of viability. After cryopreservation by means of vitrification of garlic meristems of â€˜Manuylivskyyâ€™ spring variety the number of regenerated plants reached (56.3 Â± 11.2)%, and â€˜Duchessâ€™ winter variety did (44.8 Â± 3.7)%. For the cultivation of the cryopreserved garlic meristems as the phytohormone the kinetin is advisable to be used in concentration of 0.5 mg/l. It has been shown that after cryopreservation by vitrification the garlic meristems of 2â€“3 mm had the highest viability (60â€“70%). Larger meristems (3.5â€“4 mm) had a high regenerative potential but low viability (below 25%). In smaller meristems (1â€“1.5 mm) the viability rates were reduced (30â€“47%) as well as a regenerative potential. In the meristems of 0.5 mm a regenerative potential was absent. Â Probl Cryobiol Cryomed 2015; 25(1): 3-12.